2021
DOI: 10.3389/fgene.2021.680457
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization and Expression Analysis of the Na+/H+ Exchanger Gene Family in Capsicum annuum L.

Abstract: The Na+/H+ exchangers (NHXs) are a class of transporters involved in ion balance during plant growth and abiotic stress. We performed systematic bioinformatic identification and expression-characteristic analysis of CaNHX genes in pepper to provide a theoretical basis for pepper breeding and practical production. At the whole-genome level, the members of the CaNHX gene family of cultivated and wild pepper were systematically identified using bioinformatics methods. Sequence alignment and phylogenetic tree cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 55 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…Analysis of gene structures and conserved motifs showed that CrNHX s exhibited high conservation during evolution. Interestingly, in the plant monovalent cation/proton antiporters (CPAs) superfamily, the NHX families often show multi-intron characteristics compared with other ion channel gene families, for example, the cation/H + exchanger (CHX) families [ 33 , 64 ], and in other species, the introns of NHX families seem to be fairly conservative [ 23 , 24 , 65 ]. It is reported that multiple numbers of exons in genes might be positively correlated with active chromatin structures, which could represent a type of possible gene regulation pattern for epigenetic or expression complexity [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of gene structures and conserved motifs showed that CrNHX s exhibited high conservation during evolution. Interestingly, in the plant monovalent cation/proton antiporters (CPAs) superfamily, the NHX families often show multi-intron characteristics compared with other ion channel gene families, for example, the cation/H + exchanger (CHX) families [ 33 , 64 ], and in other species, the introns of NHX families seem to be fairly conservative [ 23 , 24 , 65 ]. It is reported that multiple numbers of exons in genes might be positively correlated with active chromatin structures, which could represent a type of possible gene regulation pattern for epigenetic or expression complexity [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The detailed procedure of the evolutionary analysis was conducted according to a previous report. 21…”
Section: Analysis Of the Phylogeny Treementioning
confidence: 99%
“…SOS3 activates the SOS2 protein kinase, and the SOS2-SOS3 complex then activates SOS1/NHX7 by phosphorylation to efflux Na + ions out of the cell (Halfter et al, 2000;Liu et al, 2000;Shi et al, 2003). Previous reports have documented six NHX genes in Medicago truncatula (Sandhu et al, 2018), nine NHX genes in Capsicum annuum (Luo et al, 2021), five NHX genes in Beta vulgaris (Wu et al, 2019), six NHX genes in Vitis vinifera (Ayadi et al, 2020), 10 NHX genes in Glycine max (Chen et al, 2015), eight NHX genes in Populus trichocarpa (Tian et al, 2017), 10 NHX genes in Punica granatum (Dong et al, 2021), and eight NHX genes in Actinidia chinensis were identified (Liu et al, 2023). Such variation among the NHX gene numbers of plant species indicated that gene duplications or loss events occurred during species evolution, which also provided an opportunity to expand the NHX gene family by generation functionally divert new genes (Huang et al, 2022).…”
mentioning
confidence: 99%